2020
DOI: 10.36262/widyakala.v7i1.296
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kenyamanan Termis Kota Banda Aceh Berdasarkan Temperature Humidity Index, Discomfort Index dan Humidex

Abstract: The development of a city has had an impact on decreasing the quantity of vegetation cover and green area. The purpose of this study was to determine the thermic comfort level using the Temperature Humidity Index (THI), Discomfort Index (DI), and Humidex for the Banda Aceh City and its climatological trend during the period 1985-2012. The analysis of thermic comfort level using air temperature and humidity data for the period 1989-2018. Based on THI, the index value ranged from 23.2 to 25.8 o C. Based on DI, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…We found that several studies in Indonesia used this equation to measure thermal comfort in an urban ecosystem. In highly populated cities, the THI value rose higher in less vegetated areas [37][38][39].…”
Section: Creating Thermal Comfortmentioning
confidence: 99%
“…We found that several studies in Indonesia used this equation to measure thermal comfort in an urban ecosystem. In highly populated cities, the THI value rose higher in less vegetated areas [37][38][39].…”
Section: Creating Thermal Comfortmentioning
confidence: 99%
“…Sejalan dengan pernyataan Lakitan (1994) bahwa variasi suhu di Indonesia dipengaruhi oleh altitude (ketinggian tempat) dimana semakin rendah altitude maka suhu akan semakin tinggi. Suhu udara merupakan salah satu faktor kenyamanan termal (Siregar et al, 2020) yang akan bedampak pada kenyamanan wisata di kawasan mangrove. Peningkatan suhu udara menyebabkan berkurangnya rasa kenyamanan (Isnoor et al, 2021).…”
Section: Pendahuluanunclassified
“…Kondisi kenyamanan yang dirasakan manusia sangat bervariasi dan memiliki subjektifitas yang tinggi. Kondisi ini berkaitan dengan jenis kenyamanan fisiologis manusia terhadap lingkungan sekitarnya [7].…”
Section: Abstrakunclassified
“…Metode Humidex memiliki kelebihan pada prakteknya yang mudah digunakan serta dapat diasosiasikan langsung dengan suhu yang dirasakan oleh manusia [2][10] [18]. Pada penelitian yang dilakukan oleh [2] dan [7] menggunakan metode Humidex yang memiliki basis kenyamanan fisiologis menunjukkan bahwa kondisi kenyamanan termis pada kedua lokasi secara umum masuk dalam kategori tidak nyaman yang dirasakan oleh 50 % populasi hingga seluruh populasi. Penelitian humidex telah dilakukan oleh [12] untuk mengetahui tingkat ketidaknyamanan akibat adanya perubahan iklim.…”
Section: Pendahuluanunclassified